Bland experimentalister! - Pettersson, Helena (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2011)
This article highlights pivotal turns that might take place while collect data during ethnographic fieldwork. The author discuss how a thorough fieldwork among experimental plasma physicists and the ethnographic fieldwork in relation to Rheinberger’s concept experimental systems and how ethnography as such can be understood from the angle of being experimental.